2019
DOI: 10.1111/ajr.12508
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation for severe aortic stenosis in the Australian regional population

Abstract: Objective: To compare clinical and functional outcomes of regional and urban patients after transcatheter aortic valve implantation for severe aortic stenosis. Methods: Data were collected at patient follow-up post-transcatheter aortic valve implantation at 30 days and 12 months. Patients were stratified by residential postcodes into remoteness areas using the Australian Statistical Geography Standard. Design: Retrospective cohort study.Setting: Single-centre tertiary referral hospital.Participants: Patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Mok et al 99 identified a decreased distance in the 6-min walking test (6MWT – with a cut-off distance of less than 170 m) as a predictor of futility in patients undergoing TAVI. Paleri et al 100 used the Clinical Frailty Scale (CFS) to assess frailty and when associated with the functional NYHA class found that frailty was a marker for absence of functional improvement. In another study conducted by Yoshijima et al 101 CFS proved to be predictive of poor symptomatic benefit at 1 year after TAVI.…”
Section: The Role Of Frailtymentioning
confidence: 99%
“…Mok et al 99 identified a decreased distance in the 6-min walking test (6MWT – with a cut-off distance of less than 170 m) as a predictor of futility in patients undergoing TAVI. Paleri et al 100 used the Clinical Frailty Scale (CFS) to assess frailty and when associated with the functional NYHA class found that frailty was a marker for absence of functional improvement. In another study conducted by Yoshijima et al 101 CFS proved to be predictive of poor symptomatic benefit at 1 year after TAVI.…”
Section: The Role Of Frailtymentioning
confidence: 99%
“…A single-centre study of 142 patients consisting of 54% from regional Australia and 13% from outer regional Australia found no differences in procedural success and 30-day or 12-month mortality rates between regional and urban patients. [ 29 ] Importantly, these were regional patients who had to travel to a tertiary referral hospital to undergo their procedure.…”
Section: Access To Care and Service Deliverymentioning
confidence: 99%